2017
DOI: 10.1093/jxb/erx203
|View full text |Cite
|
Sign up to set email alerts
|

Variations in chloroplast movement and chlorophyll fluorescence among chloroplast division mutants under light stress

Abstract: Chloroplast division mutants with enlarged chloroplasts or heterogeneous chloroplast populations differ markedly from the wild type in their photorelocation efficiency and/or photosynthetic capacity under high or fluctuating light intensities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 89 publications
(156 reference statements)
0
31
0
Order By: Relevance
“…7, 8). An overall absorbance increase contradicts to slow chloroplast motion, involving a spectrally broad Δ A decrease demonstrating a light-avoidance strategy (Deamer et al 1967; Brugnoli and Björkman 1992; Dutta et al 2017). The slow Δ A increase is further spectrally distinctive from chloroplast motion due to the lack of strong peak features in the 400–500 nm region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7, 8). An overall absorbance increase contradicts to slow chloroplast motion, involving a spectrally broad Δ A decrease demonstrating a light-avoidance strategy (Deamer et al 1967; Brugnoli and Björkman 1992; Dutta et al 2017). The slow Δ A increase is further spectrally distinctive from chloroplast motion due to the lack of strong peak features in the 400–500 nm region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While the adaptive advantage of chloroplast size variation has not been investigated, experiments with Arabidopsis ftsZ and other chloroplast-division mutants have shown that plants with greatly enlarged chloroplasts exhibit defects in chloroplast movement and impairment of some photosynthetic responses as well as reduced mesophyll conductance, and that somewhat altered responses could also be observed in division mutants with less dramatic phenotypes, including ftsZ2-2 (Jeong et al, 2002;Austin and Webber, 2005;Königer et al, 2008;Dutta et al, 2015Dutta et al, , 2017Weise et al, 2015;Xiong et al, 2017). These results, along with the influence of environmental factors on chloroplast size and number discussed above, suggest that fine-tuning of chloroplast size is important for physiological fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, there are other drawbacks to having large chloroplasts. It was previously found that plants with larger-than-normal chloroplasts accumulate more photosystem II photodamage, independent of their chloroplast movement impairment (Dutta et al 2017). However, the fad5 mutation does not seem to have any alleviating effect on photosynthetic activity in the crl mutant.…”
Section: Wt Crl Crl Fad5mentioning
confidence: 96%
“…(Arabidopsis thaliana) chloroplast-division mutants that have abnormally large chloroplasts have been around for quite some time, not only because they can be identified relatively easily through screening (Pyke & Leech 1991) and because their spectacular morphology sparks intrigue, but because they have proven useful to this day for studying several important biological phenomena related not just to chloroplast division, but to control of cell size, chloroplast movement and light avoidance, and photosynthesis (Dutta et al 2017). "Giant chloroplast"…”
Section: Arabidopsismentioning
confidence: 99%